Renal Protection of in vivo administration of Tempol in streptozotocin-induced Diabetic Rats - Luan, Jiajie (2012)
The present study was carried out to investigate the protective effects of tempol on renal function and the underlying mechanism in streptozotocin-induced diabetic rats. The diabetic rats were randomly divided into Model group (without tempol) and Tempol group. Nondiabetic rats were served as Control group. The mRNA expression of canonical transient receptor potential 6 (TRPC6), transforming growth factor (TGF)-β(1) and type IV collagen (Col IV) were examined. The malondialdehyde (MDA) level, activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) in renal tissues were measured to assess redox status in kidneys. We found that tempol significantly reduced 24-h urine output and urine albuminuria excretion in the diabetic rats. Compared with the model group, the concentration of MDA was significantly lower in tempol group. In addition, diabetes decreased activities of SOD and GSH-Px and these responses were prevented by tempol treatment. Moreover, in diabetic rats, the mRNA expression levels of TGF-β(1) and Col IV were upregulated. TRPC6 mRNA expression level was downregulated in diabetic kidneys. However, all of these diabetic effects were significantly suppressed by tempol treatment. These results suggest that chronic treatment of diabetic rats with tempol can protect kidneys, possibly by reducing expression of TGF-β1, Col IV, and TRPC6.